Multiproxy study of the last meal of a mid-Holocene Oyogos Yar horse, Sakha Republic, Russia. (October 2014) - Gravendeel, Barbara; Protopopov, Albert; Bull, Ian; Duijm, Elza; Gill, Fiona; Nieman, Aline; Rudaya, Natalia; Tikhonov, Alexei N; Trofimova, Svetlana; van Reenen, Guido BA; Vos, Rutger; Zhilich, Snezhana; et al.
The last meal of a horse that lived in the northern part of the Sakha Republic (Russia) c . 5400 years ago was studied using pollen, spores, botanical macroremains, lipid composition, and ancient DNA in order to reconstruct its components. Pollen of Poaceae was superabundant, but this may be because of over-representation as a consequence of grazed inflorescenses of grasses. We evaluate the paleo-environmental indicator value of the different methods applied. Botanical macrofossils and chemical data show what the animal had eaten. Pollen grains and the aDNA record also give information about taxa that occurred elsewhere in the landscape. The combined data point to an open landscape of a coastal tundra dominated by graminoids (Poaceae, Cyperaceae) with a limited amount of Birch and Alder.